2022
DOI: 10.1002/bdr2.2082
|View full text |Cite
|
Sign up to set email alerts
|

Preconception paternal comorbidities and offspring birth defects: Analysis of a large national data set

Abstract: Background Despite the fact that the father contributes half the genome to a child, associations between paternal factors and birth defects are poorly understood. Objectives To investigate the association between preconception paternal health and birth defects in the offspring. Materials and Methods We conducted analysis of a national cohort study utilizing the IBM Marketscan Research Database, which includes data on reimbursed private healthcare claims in the United States from 2007 to 2016. The potential ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Paternal obesity and its associated metabolic disturbances are common diseases found in fathers that have the potential to cause adverse alterations in sperm epigenetics including DNA methylation and sperm mRNA profiles 9,10 . Recently it has been shown that fathers with more metabolic syndrome‐related comorbidities are at higher risk of fathering children with cardiac and respiratory defects 11 . However, the association of a father's health with his children beyond the perinatal and infant (i.e., until age one 12 ) periods remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Paternal obesity and its associated metabolic disturbances are common diseases found in fathers that have the potential to cause adverse alterations in sperm epigenetics including DNA methylation and sperm mRNA profiles 9,10 . Recently it has been shown that fathers with more metabolic syndrome‐related comorbidities are at higher risk of fathering children with cardiac and respiratory defects 11 . However, the association of a father's health with his children beyond the perinatal and infant (i.e., until age one 12 ) periods remains uncertain.…”
Section: Introductionmentioning
confidence: 99%